In situ Immune Signatures and Microbial Load at the Nasopharyngeal Interface in Children With Acute Respiratory Infection - Fukutani, Kiyoshi F.; Nascimento-Carvalho, Cristiana M.; Bouzas, Maiara L.; Oliveira, Juliana R.; Barral, Aldina; Dierckx, Tim; Khouri, Ricardo; Nakaya, Helder I.; Andrade, Bruno B.; Van Weyenbergh, Johan; de Oliveira, Camila I. (Frontiers in Microbiology, 2018)
Acute Respiratory Infection (ARI) is the most frequent cause for hospitalization in infants and young children. Using multiplexed nCounter technology to digitally quantify 600 human mRNAs in parallel with 14 virus- and 5 bacterium-specific RNAs, we characterized viral and bacterial presence in nasopharyngeal aspirates (NPA) of 58 children with ARI and determined the corresponding in situ immune profiles. NPAs were classified as bacterial (n=27), viral (n=5), codetection (presenting both viral and bacterial transcripts (n=21) or indeterminate (microbial load below threshold) (n=5). We then identified Differentially Expressed Immune Transcripts (DEITs) comparing NPAs from symptomatic children vs. healthy controls and comparing children presenting NPAs with detectable microbial load vs. indeterminate. We observed a strong innate immune response in NPAs, with the presence mostly of evolutionary conserved type I IFN-stimulated genes (ISG) which correlated with total bacterial and/or viral load. In contrast, in comparisons with indeterminate NPAs, adaptive immunity transcripts discriminated among viral, bacterial and codetected microbial profiles. In viral NPAs, B-cell transcripts were significantly enriched among DEITs, whereas only type III IFN was correlated with viral load. In bacterial NPAs, myeloid and co-inhibitory transcripts were enriched and significantly correlated with bacterial load. In conclusion, digital nCounter transcriptomics provides a microbial and immunological in situ “snapshot” at the nasopharyngeal interface in children with ARI, enabling the discrimination viral, bacterial, codetection and indeterminate samples using non-invasive sampling. Keywords: network analysis, ARI, immune response, nCounter, interferon, viral load, innate immunity, adaptive immunity.